Ectopic spleen and liver hemangioma mimicking metastatic pancreatic neuroendocrine tumor. (2015) - Engler, Christine C.; Lemke, Johannes; Kornmann, Marko; Barth, Thomas F.; Schmidt, Stefan A.; Henne-Bruns, Doris
Highlights: IPAS (intrapancreatic accessory spleen) can mimic pancreatic neuroendocrine tumors in nuclear imaging, such as Dotatate PET-CT, due to somatostatine-receptor positivity of intrasplenic lymphocytes. Non-invasive differentiation between intrapancreatic accessory spleens and pancreatic neuroendocrine tumors can be provided by using 99m Tc-sulphur-colloid or 99m Tc-tagged heat-damaged RBC Scintigraphy. Extended preoperative radiological and nuclear medical examinations play a key role in properly differentiating suspect intrapancreatic lesions from intrapancreatic accessory spleens and prevent patients from unnecessary surgery. We consider intrapancreatic accessory spleens a relevant differential diagnosis in patients with suspected pancreatic neuroendocrine tumors of the pancreatic tail, which should be taken into account before surgery is provided. Abstract: Pancreatic tumors comprise benign lesion and malignant lesion, most importantly pancreatic adenocarcinoma, acinar cell carcinoma, neuroendocrine carcinoma or metastasis. Surgical resection provides the only chance for cure for malignant pancreatic tumors. In some cases, surgical resection is performed because a malignant lesion is suspected, however, histopathological examinations eventually reveal a benign lesion. Here, we report the case of a 49-year-old woman, who was initially diagnosed with a neuroendocrine tumor of the pancreas with metastasis to the liver. The patient underwent distal pancreatectomy and atypical liver resection. Surprisingly, however, histopathological examination revealed an intrapancreatic accessory spleen (IPAS) of the pancreatic tail as well as liver hemangioma. This unique case report highlights the impact of extensive preoperative examinations to differentiate benign and malignant pancreatic lesions and, possibly, prevent patients from unnecessary surgery.